Uh oh! Wolfram|Alpha doesn't run without JavaScript.
Please enable JavaScript. If you don't know how, you can find instructions
here
.
Once you've done that, refresh this page to start using Wolfram|Alpha.
All Examples
›
Pro Features
›
Step-by-Step Solutions
›
Browse Examples
Pro
Examples for
Step-by-Step Differential Equations
Separable Equations
See how to solve separable differential equations step by step:
solve y' = y^2 x
y'(x) = (x + 2) e^(-y(x)), y(0) = 0
sec(y(t)) y'(t) + sin(t - y(t)) = sin(t + y(t))
First-Order Exact Equations
Solve exact differential equations step by step:
(3x + 2y)y' + 2x + 3y = 0 where y(0) = 2
solve t + arctan(y(t)) + (t + y(t))/(1 + y(t)^2) y'(t) = 0
Use an integrating factor to transform an equation into an exact equation:
2 t exp(2y)y' = 3 t^4 + exp(2y)
Chini-Type Equations
Solve a Riccati equation step by step:
x^2 v'(x) + 2 x v(x) = x^4 v(x)^2 + 4
solve y' = y^2/x^2 - y/x + 1, y(1) = 0
Solve an Abel equation of the first kind with a constant invariant:
y'(x) = e^(2x) x y(x)^3 - y(x) - x e^(-x), y(0) = 0
Solve a Chini equation with a constant invariant:
2 x'(t) + t = 4sqrt(x(t))
Reduction of Order
Reduce to a first-order equation:
t x''(t) - 2 x'(t) = 10 t^4
y''(x) + y'(x)^2 = 0
Derive the equation of a catenary curve step by step:
solve v''(x)^2 = (1+v'(x)^2), v(0) = 1, v'(0) = 0
Higher-Order Equations
See the steps for solving higher-order differential equations:
solve y''''(x) + 16y(x) = 0
y''' - 2y'' + y' = 2 - 24e^t + 40e^(5t), y(0) = 1, y'(0) = 0, y''(0) = -1
y''' - y'' + y' - y = cosh(x)
y''''''(t) - 4y'''''(t) + 7y''''(t) - 4y'''(t) - 4y''(t) + 8y'(t) - 4y(t) = 0
First-Order Linear Equations
Solve first-order linear differential equations:
y'(t) - 2y(t) = 3 e^(2t)
x y'(x) - 4 y(x) = x^6 exp(x), y(1) = 0
See the steps for using Laplace transforms to solve an ordinary differential equation (ODE):
solve y'(t) - 3y(t) = delta(t - 2), where y(0) = 0
Bernoulli Equations
Explore the steps to solve Bernoulli equations:
y'(x) - y = e^x y^2
x'(t) = x(t)(t x(t)^3 - 1)
solve y' + 5y = x y^4
General First-Order Equations
See the steps for solving Clairaut's equation:
y(x) = x y'(x) + y'(x)^2
Solve d'Alembert's equation:
x(t) = t x'(t)^2 + x'(t)
See how first-order ODEs are solved:
solve y' = 2((y + 2)/(x + y - 1))^2, y(1) = 0
t y(t) (1 + t y(t)^2) y'(t) = 1
Euler–Cauchy Equations
Solve Euler–Cauchy equations:
solve x^2 y''(x) - x y'(x) + y(x) = 0
x^2 y'' - y = 0
2t^2*y'' + t*y' - 3*y = t, y(1) = 0, y'(1) = 1
RELATED EXAMPLES
Differential Equations
First-Order Substitutions
Solve a first-order homogeneous equation through a substitution:
solve x y' = y*(log(x) - log(y))
Learn the steps to make general substitutions:
solve 2 t^3 y'(t) = 1 + sqrt(1 + 4 t^2 y(t))
y'(x) = (1-x cos(y(x))) cot(y(x))
Second-Order Constant-Coefficient Linear Equations
Solve a constant-coefficient linear homogeneous equation:
x''(t) = -k x(t)
solve y''(t) + 5y'(t) + 6y(t) = 0, y(0) = 1, y'(0) = 0
Explore how to solve inhomogeneous constant-coefficient linear equations:
solve y''+ y = sin(2x)
x'' - 2x' - 8x = 3e^(-2t), x(0) = 0, x'(0) = 1
See the steps for using Laplace transforms to solve an ODE:
y''(t) + 2 y'(t) + 2 y(t) = cos(t) delta(t - 3 pi), y(0) = 1, y'(0) = -1
General Second-Order Equations
Investigate the steps for solving second-order ODEs:
t y''(t) - t y'(t) + y(t) = 2, y(0) = 2, y'(0) = -4
y'' - 2 cot(x) y' + (1+2cot(x)^2) y = 0
y''(x) + tan(x) y'(x) + sec(x)^2 y(x)==0
x^4*y*y'' + x^4*y'*y' + 3*x^3*y*y' = 1
solve y''(t) + sin(y(t)) = 0
x^2y'' + xy' + (x^2-1/4)y=0
solve (1-x) y'' + x y' - y = 0
Go
Pro
Now
Learn more about Wolfram|Alpha Pro »